The Multifaced Politics: A Study on Polarization of Political Behavior of Tarekat Community in West Sumatera, Indonesia - Welhendri Azwar; Muliono Muliono (Al-Jami'ah: Journal of Islamic Studies, 2022)
Tuanku as a leader of Tarekat community is a charismatic figure who plays significant socio-political roles. He is still placed as source of "fatwa" to political choice of the community. This study is used descriptive-phenomenological methods. To understand the meaning of Tarekat community towards to various socio-political activities and patterns of social relations between Tarekat community with society, researchers conducted a focus group discussions and in-depth interviews with the Tarekat community. Observations were carried out to pay attention both political behavior of Tarekat community and socio-political dynamic of the society related to the religious teachings and understandings where Tarekat activities are practiced. This study elucidates facts; first, the political behavior of Tarekat community in West Sumatra revealed a strong influence the relations between teacher and student on political choices of Tarekat community and showed the diversity typologies of Tarekat political behavior. Second, in the context of understanding religious struggle of Tarekat in the midst of socio-political dynamics in West Sumatra, Tarekat community consistently develop lithe and flexible behaviors and activities in socio-politic. This study is important to understand the political behavior of Tarekat community in the vortex of political identity in the political dynamics that occur, and always change.[Tuanku sebagai pimpinan kaum Tarekat merupakan sosok karismatik yang memainkan peran-peran sosial-politiknya secara signifikan. Ia masih ditempatkan sebagai sumber “fatwa” untuk pilihan politik masyarakat. Penelitian ini menggunakan metode deskriptif-fenomenologi. Untuk memahami makna (meaning) kaum Tarekat terhadap berbagai aktivitas sosial-politik dan corak hubungan sosial kaum Tarekat dengan masyarakat, peneliti melakukan focus group discussion dan wawancara mendalam (indepth interview) kepada kaum Tarekat. Observasi dilakukan untuk memperhatikan perilaku politik kaum Tarekat dan keadaan sosial politik masyarakat yang berkaitan dengan ajaran dan paham keagamaan Tarekat dimana aktivitas Tarekat dipraktekkan. Kajian ini menguraikan fakta bahwa;  pertama, perilaku politik kaum Tarekat di Sumatera Barat menampakkan wujud pengaruh kuat hubungan guru-murid terhadap pilihan politik kaum Tarekat dan memperlihatkan keragaman dinamis tipologi perilaku politik kaum Tarekat. Kedua, dalam konteks pergumulan paham keagamaan kaum Tarekat di tengah dinamika sosial politik di Sumatera Barat, kaum Tarekat konsisten mengembangkan perilaku dan aktivitas sosial-politik yang lentur dan fleksibel. Kajian ini menarik dan berguna memahami perilaku politik kauam Tarekat ditengah pusaran politik identitas dalam dinamika politik yang terjadi, dan senantiasa berubah.]